Pengaruh Media Sosial, Display Product dan Brand Awareness terhadap Minat Beli Konsumen (Studi Kasus pada Indomaret Pondok-Sukoharjo) - Ainaro Adi Sutomo; Agus Suyatno; Esti Dwi Rahmawati (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
Indomaret is a retail company that has been established for a long time in Indonesia, one of the retail companies that pays attention to and takes care of consumers. Indomaret pays close attention to the use of social media, product displays and growing brand awareness among the general public. In this case, Indomaret uses a method that has been known as online marketing using Instagram social media, where Instagram has strong enough access to bring consumers to stop by the store to make a buying and selling transaction. Indomaret has also updated the planogram program which is useful to make it easier for consumers to pick up the products consumers want to buy. Indomaret also continues to post or share interesting content on Instagram that is useful for the future or spoils consumers for shopping at Indomaret. In this study the method used by researchers divided it into two, namely the first is the method of data collection including observation, interviews, literature study and documentation. The second is the distribution of questionnaires in which there are several consumers who order online. The conclusion regarding the development of a social media system for marketing products, product display is carried out in the display rack planogram update. Brand awareness is needed to be more famous among the people.